Sending retirees to the frontlines? - Bruce F. Sabath; Henri G. Colt (Greater Baltimore Medical Center, 2020)
Facing an unprecedented surge of patient volumes and acuity, institutions around the globe called for volunteer healthcare workers to aid in the effort against COVID-19. Specifically being sought out are retirees. But retired healthcare workers are taking on significant risk to themselves in answering these calls. Aside from the risks that come from being on the frontlines of the epidemic, they are also at risk due to their age and the comorbidities that often accompany age. If, for current or future COVID efforts, we as a society will be so bold as to exhort a vulnerable population to take on further risk, we must use much care and attention in how we involve them in this effort. Herein we describe the multifaceted nature of the risks that retired healthcare workers are taking by entering the COVID-19 workforce as well as suggest ways in which we might take advantage of their medical skills and altruism yet while optimizing caution and safety.